Ether in Biquaternionic Presentatioin, Its Density and Properties - LA, Alexeyeva (Annals of Mathematics and Physics, 2025)
The biquaternionic model of the ether is presented as electro-gravimagnetic field, the state of which is described by the EGM strength biquaternion. Its complex scalar part determines the density of the ether, and the complex vector part characterizes the strength of the electric and gravimagnetic fields. The biquaternion gradient of the EGM strength biquaternion determines the biquaternion of EGM charge-current, which contains in the scalar part the electric charge and gravitational mass, and the vector part is formed by electric and gravimagnetic currents. This biquaternion wave equation (biwave Eq) is generalization of Maxwell equations. The field’s analogue of the three Newton’s laws are presented in form of biwave equations. Representations of biquaternion of photons and elementary atoms are obtained as partial stationary solutions of biwave equations with a fixed oscillation frequency. The presence of a gravitational component of the EGM field of the photon is shown, which explains the light pressure A field analogue of Newton's second law is presented as a biquaternion generalization of the Dirac system of equations. It describes the transformation of the EGM charge-current biquaternion under the influence of an external EGM field. It contains, in addition to all known physical forces, a number of new forces that are proposed for discussion and experimental verification. The biquaternion representation of Newton's third law of action and reaction in the scalar part is a well-known analogue of Bettie’s law on the power of forces acting on EGM charges and currents. Using the biquaternion model of the atom, a periodic system of atoms is constructed based on the structure of a simple musical scale.